The Politics of Samuel Johnson
XIV, 235 p.
Keywords: A major academic controversy has raged in recent years over the analysis of the political and religious commitments of Samuel Johnson, the most commanding of the 'commanding heights' of eighteenth-century English letters. This book, one of a trilogy from Palgrave, brings that debate to a decisive conclusion, retrieving the 'historic Johnson.'.